2015
DOI: 10.1002/eco.1666
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of long‐term soil water dynamics at Reynolds Creek, Idaho: implications for rangeland productivity

Abstract: Plant productivity, forage availability and soil carbon dynamics are all strongly controlled by soil water in semi-arid rangelands. Sagebrush steppe ecosystems are among the most extensive in the western USA. We used the soil ecohydrology model (SEM) to simulate soil water dynamics and estimate plant growth at three different sagebrush steppe sites. SEM is a capacitance parameter model that uses a water balance approach to simulate daily changes in soil water and a modification of the de Wit equation to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Engda et al (2016) found early growing season soil water to be a reasonable predictor of growing‐season herbage production for Wyoming rangelands. A similar finding has been reported for an Idaho rangeland (Finzel et al, 2016). Soil water content therefore provides useful information to assess drought conditions.…”
supporting
confidence: 89%
“…Engda et al (2016) found early growing season soil water to be a reasonable predictor of growing‐season herbage production for Wyoming rangelands. A similar finding has been reported for an Idaho rangeland (Finzel et al, 2016). Soil water content therefore provides useful information to assess drought conditions.…”
supporting
confidence: 89%
“…Second, for many ecohydrological and biogeochemical processes, the measured θ at a given depth is not necessarily the value of interest and may, in fact, be misleading because differences in soil texture may obscure important soil water potential differences. In terms of soil water measurements, parameters of field capacity (θ FC ) and the plant extraction limit, θ PEL , are useful for hydrologic purposes (Finzel et al., 2016; Seyfried & Wilcox, 2006) and can be identified from field data (Chandler et al., 2017). Similarly, levels of microbial activity are also better described by θ values normalized to the same parameters of θ PEL , θ FC in addition to the saturated value of θ SAT (Moyano, 2013; Paul et al., 2003), and not the actual θ value.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution and function of vegetation within the RCEW are strongly controlled by terrain, precipitation, and soil moisture availability (Finzel et al. ). Across middle and upper elevations of the watershed, highly productive aspen stands are often distributed along leeward slopes and we hypothesize that they utilize water subsidies stemming from large snow drifts that persist late into the spring months (Seyfried et al.…”
Section: Methodsmentioning
confidence: 99%